Lineage Switch in an Infant B-Lymphoblastic Leukemia With t(1;11)(p32;q23); KMT2A/EPS15, Following Blinatumomab Therapy. (August 2021) - Du, Jing; Chisholm, Karen M; Tsuchiya, Karen; Leger, Kasey; Lee, Brittany M; Rutledge, Joe C; Paschal, Cate R; Summers, Corinne; Xu, Min
We report a 6 month-old infant girl with t(1;11)(p32;q23), KMT2A/EPS15 -rearranged B-acute lymphoblastic leukemia (B-ALL) that was refractory to traditional ALL-directed chemotherapy. Following administration of blinatumomab, she experienced lineage switch from B-ALL to acute myeloid leukemia (AML). Myeloid-directed chemotherapy resulted in clearance of AML by flow cytometry, though a residual CD19+ B-ALL population persisted (0.14%). Following bridging blinatumomab, the patient achieved B-ALL and AML remission, as measured by flow cytometry. The patient subsequently underwent allogeneic hematopoietic stem cell transplant. Unfortunately, she relapsed with CD19+ B-ALL one-month post-transplantation. Next generation sequencing study of IGH/IGL using ClonoSEQ® analysis detected 3 dominant sequences all present in her original B-ALL, lineage switched AML, and post-transplant relapsed B-ALL, though the latter showed an additional 4 sequences, three of which were present at low abundance in the original diagnostic sample. The presence of the same clones throughout her disease course suggests cellular reprogramming and differentiation following chemotherapy and immunotherapy. This is the first reported case of lineage switch of B-ALL with t(1;11) and also the first report of a lineage switch case that used ClonoSEQ® to define the clonality of the original B-ALL, lineage switched AML, and relapsed B-ALL.